Assessing an ecological security network for a rapid urbanization region in Eastern China. (29th March 2021) - Zhou, De; Lin, Zhulu; Ma, Siming; Qi, Jialing; Yan, Tingting
Abstract: Rapid urbanization leads to fragmentation of landscape and destruction of the ecological security network. A sound ecological security network promotes connectivity between ecological sources and mitigates the degradation of an ecological system. However, when identifying the ecological sources of the ecological network, studies available in the current literature did not simultaneously consider the structures, functions, and values of ecological patches. Our study aimed to fill this research gap, and our objective was to improve the framework for assessing the ecological security network. We demonstrated the application of the proposed framework through a case‐study of the urban agglomeration around Hangzhou Bay (UAHB), a rapid urbanization region in Eastern China. We improved the identification method of ecological sources by integrating the evaluations of ecosystem services value and ecological sensitivity, while we screened ecological sources by using the rank‐size rule and the natural breaks method. Based on the screened ecological sources, the ecological corridors were reconstructed and optimized for the UAHB region. The results from this study showed that ecological network has actually improved in the UAHB in the last 20 years. However, the structure and function of the ecological security network were strongly influenced by human activities and urban sprawl. The ecological security network has deteriorated locally in eastern coastal areas of UAHB during the past 20 years with strong spatial variability in ecological security patterns. To maintain an environment with well‐protected ecological quality, we proposed a set of five measures to improve the sustainable development of the ecological system.